Analisis Korelasi antara Nilai UTS dan Nilai UAS Siswa: Studi pada Mata Pelajaran Matematika Kelas XI SMK Bhakti Kencana Bandung (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Assessment of learning outcomes plays a crucial role in evaluating students' academic achievement. Midterm and final exam scores are often used as benchmarks for learning performance, yet the relationship between the two is rarely analyzed in depth. This study aims to examine the correlation between Midterm Exam (UTS) and Final Exam (UAS) scores in Mathematics among 11th-grade students at Bhakti Kencana Vocational High School in Bandung. A quantitative approach with a correlational method was employed, involving 30 students as the sample. Data were obtained through documentation of scores, and analysis was conducted using the Spearman Correlation Test due to the data not being fully normally distributed. The results indicated a significant and positive correlation between UTS and UAS scores, with a correlation coefficient of 0.511. This suggests that midterm scores can serve as a fairly reliable indicator of final exam performance and reflect the consistency of students' academic performance. The implications of these findings highlight the importance of continuous monitoring and learning efforts from mid-semester onwards to optimize students' final outcomes.